Pemanfaatan Perasan Daun Pacar Air (impatins balsamina) Sebagai Alternatif Pewarnaan Alami Pengganti Eosin 2% Pada Pemeriksaan Telur Cacing Ascaris lumbricoides - Octavia, Nur Afni Heryanti (Fakultas Kedokteran, Institut Kesehatan Deli Husada Deli Tua, 2024)
The leaves of the water henna plant (Impatien balsamina L.) contain anthocyanins. Natural dyes with an orange-reddish-brown colour are made from compounds called anthocyanins. Knowing whether the leaves of Impatiens balsamina L. can be used as a dye substitute for worm eggs is the purpose of this study. To distinguish the background contrast and make the shape and components of the worm eggs clearer, 2% eosin reagent dye was added during the testing process. Eosin 2% will produce a red color in the background of the preparation field of view .This study used an experimental method on 3 different treatment variations based on the concentration of water henna leaves (Impatients balsamina L) using distilled water in a brown bottle 20%, 10%, 5%. The results illustrate the variation of Impatients balsamina L. leaf concentration, 20%, 10%, and 5% used as an alternative dye in examining worm eggs. For each treatment modification, there was an apparent but not statistically significant variation in staining quality. The staining effect of water henna leaf juice, produces a contrasting background, allowing the dye to be absorbed by the egg, and highlighting the shape and components of the egg. In the experimental preparations, alternative staining was carried out using squeezed water and looking at the comparison of each concentration.